Sunteți pe pagina 1din 1

Differentiation Formulas

d

dx

k = 0

(1)

d

dx

[f (x) ± g(x)]

= f (x) ± g (x)

(2)

d

dx

[k · f (x)] = k ·

f (x)

 

(3)

d

dx

[f (x)g(x)] = f (x)g (x) + g(x)f (x) (4)

d

f(x) = g(x)f (x) f(x)g (x)

g(x)

[g(x)] 2

(5)

dx

d

dx

f

(g(x)) = f (g(x)) · g (x)

(6)

d

 

dx

x n = nx n1

 

(7)

d

dx

sin x = cos x

 

(8)

d

 

dx

cos x

= sin x

 

(9)

d

 

dx

tan x = sec 2 x

 

(10)

d

 

dx

cot x = csc 2 x

 

(11)

d

dx

sec x

=

sec x tan x

 

(12)

d

dx

csc x = csc x cot x

 

(13)

d

dx

e x = e x

(14)

d

dx

a x

= a x

ln a

 

(15)

d

1

dx

ln |x| =

x

(16)

d

sin 1 x =

 

1 x 2

(17)

dx

1

 

d

 

dx

cos 1 x =

1 x 2

1

 

(18)

d

tan 1 x =

2

1 + 1

(19)

dx

x

d

1

 

cot 1 x

=

(20)

dx

x

2

+ 1

d

1

(21)

dx

sec

x =

1 2 1

|x| x

d

 

dx

csc 1 x =

1 1

|x| x 2

(22)

Integration Formulas

dx = x + C

x n dx

=

n+1

x

n + 1 + C

dx

x

= ln |x| + C

e x dx = e x + C

a x dx =

ln 1 a a x + C

ln x dx = x ln x x + C

(1)

(2)

(3)

(4)

(5)

(6)

sin x dx = cos x

+ C

 

(7)

cos x dx =

sin x + C

(8)

tan x dx =

ln | cos x| + C

(9)

cot x dx

= ln | sin x| + C

(10)

sec x dx

=

ln | sec x +

tan x| + C

(11)

csc x dx = ln | csc x

+ cot x| + C

(12)

sec 2 x dx

=

tan x + C

(13)

csc 2 x dx = cot x + C

sec x tan x dx = sec x

+ C

csc x cot x dx = csc x + C

dx

x 2 = sin 1 x + C

a

a 2

dx

1

a tan 1 x + C

a 2 + x 2 =

a

dx

1

a sec 1 |x| + C

x x 2 a 2 =

a

(14)

(15)

(16)

(17)

(18)

(19)